A framework of biometric recognition and personalized mobile application to establish a dynamic connection with the ATM to enable secure transaction - Tasnim, Syeda Prima (Brac University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Science and Engineering, 2019.